2015
DOI: 10.1002/jssc.201400943
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of amino acids and neurotransmitters in plasma samples from schizophrenic patients by hydrophilic interaction liquid chromatography with tandem mass spectrometry

Abstract: A sensitive, reproducible, and rapid method was developed for the simultaneous determination of underivatized amino acids (aspartate, serine, glycine, alanine, methionine, leucine, tyrosine, and tryptophan) and neurotransmitters (glutamate and γ-aminobutyric acid) in plasma samples using hydrophilic interaction liquid chromatography coupled to triple quadrupole tandem mass spectrometry. The plasma concentrations of amino acids and neurotransmitters obtained from 35 schizophrenic patients in treatment with cloz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 48 publications
1
22
0
3
Order By: Relevance
“…Amino acids play an important role in the process of human metabolism, so they are important substances which are related to human health [1][2][3][4]. Studies have shown that amino acid metabolism diseases and malignant tumors had certain relevance to some tyrosine metabolite [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Amino acids play an important role in the process of human metabolism, so they are important substances which are related to human health [1][2][3][4]. Studies have shown that amino acid metabolism diseases and malignant tumors had certain relevance to some tyrosine metabolite [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Commonly, hydrophilic interaction chromatography (HILIC) column is widely used to analyze amino acids [18,23,[26][27][28]. HILIC column has hydrophilic polar stationary phase which can interact with highly polar compounds by strong hydrophilic interaction [18].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with GC-MS and HPLC, liquid chromatography tandem with mass spectrometry detection (LC-MS) had higher sensitivity and stability. So far, there several LC-MS methods have been reported [19][20][21][22][23]. However, some methods were used in food [21,22], some methods had high limits of detection or need derivatization to improve the chromatographic separation [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, hyphenated analytical techniques combining separation technologies with MS have become highly effective tools for small‐molecule analysis. In this regard, methods using LC–MS/MS have been reported for the analysis of several endogenous metabolites from tissue and biological systems . Nevertheless, most of these quantitative methods focus on amino acids or uremic toxins rather than the gut microbiota cometabolic pathways of aromatic amino acids.…”
Section: Introductionmentioning
confidence: 99%